Optics - Freeman, M. H. (Michael Harold) (Butterworths, 1990)
Though the basic science of optics remains the same, technology has advanced considerably since the publication of the ninth edition in 1981. This has led to an extensive revision of the text to take into accound such recent technological developments as the greater use of lasers and fibreoptics and the development of diffractive optical elements. Despite related developments in personal computers, Professor Freeman maintains that the optimum learning conditions still comprise a textbook, calculator and notepad. Optics therefore continues to make minimal mathematical demands on the reader and avoids specific techniques such as matrix algebra and complex exponent trigonometry. Optics is the basic text in optical science related to visible light, and meets the specific needs of all those seeking the optical knowledge required in optometry, ophthalmology and the visual sciences. It will also be valuable to scientists and engineers who have become newly involved in optical systems.